Esthetic soft tissue management of teeth and implants - Saadoun, Andre P. (Chichester, West Sussex : Wiley-Blackwell, 2013)
'This is a step by step guide to success in periodontics and implant dentistry, helping clinicians to create a natural and esthetically pleasing smile for their patients. Starting with a general discussion of facial esthetics and analyzing the dento-gingival constituents of the smile, the book goes on to consider the impact of these on people's quality of life, both in terms of health and social engagement. Subsequent chapters focus on specific esthetic treatments such as crown lengthening procedures, gingival recession coverage with connective tissue grafts or periodontal regenerative material and soft tissue management for natural teeth and implants'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Dental Implantation -- methods; Gingival Recession -- prevention & control; Periodontics -- Methods; Dental implants; Dentistry -- Aesthetic aspects; Periodontics